MITIGATION OF ARSENIC-INDUCED RENAL TOXICITY THROUGH PACHYPODOL IN QUAILS - SOHAIL , MA; MAJID , MS; NAWAZ , MS; HASSAN , A; NAZ , M; TAHIR , M; RAZA , N (Biological and Clinical Sciences Research Journal, 2023)
Heavy metals are abiotic toxicants that are non-biodegradable and can be propagated by human activities. Heavy metals can induce hepatotoxicity, immuno-toxicity, hemotoxicity, cardiotoxicity, neurotoxicity, and nephrotoxicity in living things. Arsenic (As) is gradually deposited into renal tissues because of its great affinity for hemoglobin, resulting in renal damage, oxidative stress, DNA, and urinary bladder damage. Pachypodol (4′, 5-dihydroxy-3, 3′, 7-trimethoxyﬂavone) is a flavonoid extracted from Pogostemon cablin and is a protective anti-oxidant. To determine renal damage markers in quails treated with arsenic, pachypodol, and a mixture of both, sixteen quails (Coturnix coturnix) were purchased from Bird's Market Jhang Bazar, Faisalabad. Birds were divided into four groups of equal size. Group-I was the control group, group-II was exposed to arsenic, group-III was co-treated with arsenic and pachypodol, and group-IV (positive) was treated with pachypodol. After 30 days, all groups of birds were sacrificed. Blood samples were collected from all groups of birds. In the current experiment, the levels of uric acid, creatinine, biliverdin, and metal accumulation were significantly (p<0.05) due to arsenic treatment but normalized as pachypodol administered. The albumin, body weight, and organ weight were observed significantly (p<0.05) lowered in arsenic treatment while regaining significantly (p<0.05) due to pachypodol treatment. Histopathological and behavioral alterations were also observed. Therefore, current research concluded that pachypodol has ameliorative potential against arsenic-induced renal damage in quails (Coturnix coturnix).